112k views
5 votes
Find (w² - w + 1) + (w³ - 2w² + 99).

User Niniki
by
4.9k points

2 Answers

6 votes

Answer:

w³ - w² - w + 100

Explanation:

The sum of (w² - w + 1) and (w³ - 2w² + 99) is:

(w² - w + 1) + (w³ - 2w² + 99)

= w² - w + 1 + w³ - 2w² + 99

= w² - 2w² - w + w³ + 99 + 1

= -w² - w + w³ + 100

= w³ - w² - w + 100

Thus, (w² - w + 1) + (w³ - 2w² + 99) = w³ - w² - w + 100.

User Ckluss
by
5.8k points
0 votes

Explanation:

Given

(w² - w + 1) + (w³ - 2w² + 99)

Now opening the bracket we get

w² - w + 1 + w³ - 2w² + 99

Re arranging,

w³- 2w²+w²- w+ 1+ 99

w³- w²- w+100

Thus the answer is w³- w²- w+100

User Trent Small
by
4.9k points